21 Profiling sow vaginal and fecal and piglet gastrointestinal microbiome and the passage of sow microbiome to their progeny from birth to weaning. (5th December 2019) - Tran, Huyen; de Rodas, Brenda; Lahoti, Manohar M; Johnson, Timothy J
Abstract: The objectives of this study were 1) to profile the sow vaginal and fecal microbiome and the corresponding piglet gastrointestinal microbiome from birth to weaning, and 2) to identify the core microbiome shared between sows and piglets. A total of 226 samples collected from sows (vaginal swabs pre-farrow; fecal samples at farrow, d 3, 7, 10, 17 post-farrow) and their progenies (stomach, ileum, and colon digesta at birth, d 2, and 14 after birth) were used for the analyses of microbial community structure using 16S rRNA V4 amplicon sequencing with Illumina MiSeq. Our data indicated that the piglet and sow microbiome were quite distinct. Piglets had lower bacterial alpha diversity (chao1, richness, Shannon, Simpson indices; P < 0.01) than sows across all timepoints. Beta diversity of piglets by sample types was significantly different (P < 0.001) than sows by sample types when averaged across all timepoints or separation by timepoints. Feature selection by the Linear discriminant analysis effect size (LEfSe) indicated that the genera associated with piglets included those classified as Lactobacillus, unclassified Micrococcaceae, and Rothia when averaged across sampling points and sample types. Genera associated with sows included those classified as Treponema, YRC22, Unclassified RF39, Unclassified Christensenellaceae, Turicibacter, Unclassified RFP12, Unclassified F16, Collinsella, Coprococcus, Unclassified Coriobacteriaceae, and Unclassified Mogibacteriaceae. The genera shared between sow vaginal samples and piglets included those classified as Bacteroides, Fusobacterium, Haemophilus, Prevotella, Veillonella, and unclassified Clostridiadiaceae. The genera shared between sow fecal and piglet samples included those classified as Bacteroides, Lactobacillus, unclassified Clostridiadiaceae, unclassified Ruminococceae, and Prevotella. Overall, there are evidences that bacterial genera were passed from sows to piglets and influenced the microbial communities of piglets later in life.